2010
DOI: 10.1213/ane.0b013e3181c88f27
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Sciatic Nerve Block in the Popliteal Fossa Using a Lateral Approach: Onset Time Comparing Separate Tibial and Common Peroneal Nerve Injections Versus Injecting Proximal to the Bifurcation

Abstract: Blocking the tibial and common peroneal nerves in the popliteal fossa separately provides for a faster onset than a prebifurcation sciatic block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 8 publications
3
34
2
Order By: Relevance
“…When the SN is blocked with the lateral approach in the supine position, the onset of block, as assessed by pin prick, is faster in the area innervated by the common peroneal nerve than that by the tibial nerve [3]. In our study, there was no significant difference in the onset of sensory block between the tibial and common peroneal nerves.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…When the SN is blocked with the lateral approach in the supine position, the onset of block, as assessed by pin prick, is faster in the area innervated by the common peroneal nerve than that by the tibial nerve [3]. In our study, there was no significant difference in the onset of sensory block between the tibial and common peroneal nerves.…”
Section: Discussioncontrasting
confidence: 53%
“…Buys et al [3] reported that the block performance time of ultrasound guided SNB with the lateral approach in the supine position, which was defined as the time elapsed from the insertion of the block needle until the completion of local anesthetic injection, was 2.9 ± 1.7 (mean ± SD) min. Prasad et al [5] reported that the block performance time of ultrasound guided SNB with the lateral approach in the prone position, which was defined as the time elapsed from ultrasound transducer preparation until the completion of anesthetic injection, was 9±3 (mean ± SD) min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies have yielded different results regarding the location of the tibial nerve (TN) and common peroneal nerve (CPN) bifurcation in the popliteal fossa, but the depth and location of the nerves passing over the popliteal crease were not measured and it was unclear whether the perineurium was preserved during dissection. Of various methods used for PopNB, blocking the targeting nerve separately provides fast and effective results with patient satisfaction (Buys et al, 2010;Paqueron et al, 1999). The posterior approach is reported to be easy for supine positioning with short needle distance to reach the target structure (Khabiri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These two approaches to injections at the sciatic nerve are referred to collectively as prebifurcation blocks. However, some papers (Buys et al, 2010;Paqueron et al, 1999) reported that blocking the TN and CPN separately provides a faster onset than a prebifurcation block.…”
Section: Introductionmentioning
confidence: 99%